Relationship between cognitive functions and agility performance in elite young male soccer players - Matlák, J.; Fridvalszki, M.; Kóródi, V.; Szamosszegi, G.; Pólyán, E.; Kovács, B.; Kolozs, B.; Langmár, G.; Rácz, L. (The Journal of Strength and Conditioning Research, 2024)
The aim of this study was to assess the relationship between agility performance and cognitive functions measured under laboratory conditions among elite young soccer players. Twenty-five, elite, young, male soccer players (12.3 ± 0.4 years, 155.4 ± 7.6 cm, 42.6 ± 6.9 kg) completed a battery of field tests, including 5-, 10-, 20-m sprints, change of direction speed (CODS), standing long jump, and an agility test based on a human stimulus. Subjects also completed choice reaction (RT, S3) and reactive stress tolerance (DT, S1) tests on the Vienna Test System. There was a moderate significant relationship (p < 0.05) found between mean reaction time and mean motor time during the choice reaction task and decision time in the agility test. Decision time also showed a large significant correlation (p < 0.05) with total time in the agility test. No significant correlation was found between total time in the agility test and variables measured during RT and DT tests. No significant correlations were found between agility test results and results from straight line sprints, CODS, and standing long jump tests. The results of this study suggest that choice reaction time is related to decision-making speed during the agility task used in this study and can have an indirect effect on agility performance in elite young soccer players. Further studies assessing the relationship between different cognitive functions and agility performance in different sports and age categories could help in the identification of determinant cognitive functions in perceptual and decision-making factors of agility.